The Application of Nursing Interventions: Generalist Therapy to Against Hopelessness on Elderly - Ike Mardiati Agustin; Budi Anna Keliat; Mustikasari Mustikasari (Jurnal Ners, 2015)
Introduction: An increasing number of elderly people followed the emergence of mental health problems. One of mental health problem that arises is hopelesness. Nursing action to hopelesness in elderly people in society is not to optimals. The aimed of this paper was gave an overview about the application of nursing intervention: generalist therapy to against hopelesness on elderly. Method: This research was used descriptive analytic design. Population were elders who lived at RW 3 and RW 4, Kelurahan Ciwaringin, Kota Bogor. Samples were 10 respondents, taken according to purposive sampling technique. Independent variable was generalist therapy, while dependent variables were sign and symptoms of hopelessness and ability to cope with hopelessness. Data were collected by using questionnaire, then analyzed by using frequency distribution.Result: The results showed that generalist therapy can decrease elder’s sign and symptoms of hopelessness (21%) and increase their ability to cope with hopelessness (72%).Discussion: It can be concluded that generalist therapy can be used as one of nursing intervention to against hopelesness in the elderly.